Respuesta :
Plug the values into the second equation to see if they end up equaling 0.
-4: 2(-4)^2 - 6(-4) - 8 = 0
2(16) + 24 - 8 = 0
32 + 16 = 0
Not -4
-1: 2(-1)^2 - 6(-1) - 8 = 0
2 + 6 - 8 = 0
8 - 8 = 0
0 = 0
Yes -1
0: 2(0)^2 - 6(0) - 8 = 0
0 - 0 - 8 = 0
Not 0
1: 2(1)^2 - 6(1) - 8 = 0
2 - 6 - 8 = 0
-12 = 0
Not 1
4: 2(4)^2 - 6(4) - 8 = 0
2(16) - 24 - 8 = 0
32 - 32 = 0
0 = 0
Yes 4 ———— Or use the quadratic equation ( - b +/- sqrt( b^2 - 4ac)) / 2a ———— a would be 2– b would be -6– & c is -8
-4: 2(-4)^2 - 6(-4) - 8 = 0
2(16) + 24 - 8 = 0
32 + 16 = 0
Not -4
-1: 2(-1)^2 - 6(-1) - 8 = 0
2 + 6 - 8 = 0
8 - 8 = 0
0 = 0
Yes -1
0: 2(0)^2 - 6(0) - 8 = 0
0 - 0 - 8 = 0
Not 0
1: 2(1)^2 - 6(1) - 8 = 0
2 - 6 - 8 = 0
-12 = 0
Not 1
4: 2(4)^2 - 6(4) - 8 = 0
2(16) - 24 - 8 = 0
32 - 32 = 0
0 = 0
Yes 4 ———— Or use the quadratic equation ( - b +/- sqrt( b^2 - 4ac)) / 2a ———— a would be 2– b would be -6– & c is -8
Answer:
x= -1 and x = 4
Step-by-step explanation:
We have to graph the quadratic function [tex]y=2x^2-6x-8[/tex] using the graphing calculator.
The graph has been attached.
Now, we have to find the solutions of the equation [tex]0=2x^2-6x-8[/tex]
For this, we see at which point (s) the graph intersects the x axis. The x coordinate of these points would be the solution.
From the attached graph we can see that the graph intersects the x-axis at (-1,0) and (4,0). Hence, the x-coordinate of these points would be the solution.
Thus, the solutions of the given equation are x= -1 and x = 4
![Ver imagen SociometricStar](https://us-static.z-dn.net/files/d7c/e09774c91e171cb4c43da1f02a97d290.png)